Anti-freezing conductive double-network hydrogel based on silk fibroin as well as preparation method and application of anti-freezing conductive double-network hydrogel

By forming a dual network structure of silk protein and lithium bromide in conductive hydrogel, the problem of decreased performance of conductive hydrogels in the ultra -low temperature environment is solved, and stable conductive and mechanical properties are achieved under extreme conditions.

CN119371681AActive Publication Date: 2025-01-28WUHAN TEXTILE UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411481948.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing conductive hydrogels have greatly reduced and even lost mechanical flexibility and sensing performance in ultra-low temperature environments, making it difficult to maintain stable conductivity and mechanical properties in harsh environments.

Method used

By mixing the mixing of silk protein and lithium bromide and heating dissolution, the symbolin/lithium bromide co -solution is formed, and the conductive substance is added under the action of the crosslierant to form a dual network structure to enhance the frost resistance and conductivity of the gel.

Benefits of technology

The obtained water gel still maintains good mechanical properties and sensitive sensing performance in the ultra-low temperature environment of -108 ° C. It is suitable for applications under extreme conditions, such as polar inspections and flexible robots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371681A_ABST
    Figure CN119371681A_ABST
Patent Text Reader

Abstract

The invention provides anti-freezing conductive double-network hydrogel based on silk fibroin as well as a preparation method and application of the anti-freezing conductive double-network hydrogel. The preparation method comprises the following steps: dissolving degummed silk in a lithium bromide solution, then adding a conductive substance, uniformly mixing, and carrying out next-step crosslinking under the action of a crosslinking agent to form the silk fibroin conductive hydrogel. The silk fibroin and the conductive substance can respectively form a cross-linked network under the action of the cross-linking agent, and in addition, an intermolecular acting force exists between the silk fibroin and the conductive substance, so that the anchoring effect of the conductive substance in the gel matrix is facilitated. The high-concentration ions in the gel and the conductive network are used as conductive media to jointly promote the sensing sensitivity and stability of the conductive hydrogel. The formation of the double networks obviously reduces the freezing point of the gel system. The hydrogel prepared in the invention has good mechanical properties, conductive sensing performance and ultrafast response / recovery time in an ultralow temperature environment, and is suitable for the ultralow temperature environment, such as the fields of human motion monitoring in polar investigation activities and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive hydrogels, and in particular to a silk fibroin-based antifreeze conductive double network hydrogel and a preparation method and application thereof. Background Art

[0002] As a kind of functional hydrogel, conductive hydrogel has good mechanical and conductive properties, can accurately convert external mechanical stimuli into recordable electrochemical signals, and has high application prospects in the manufacture of flexible electronic devices. However, in the face of harsh environments, especially ultra-low temperature conditions, the water molecules in the conductive hydrogel material will be frozen, and the brittleness of the gel will cause a significant decrease in the mechanical flexibility and sensing performance of the gel, or even a complete loss. Therefore, it is of great significance to develop conductive hydrogels with excellent antifreeze properties in ultra-low temperature environments.

[0003] In recent years, incorporating inorganic salts or ionic liquids into hydrogel matrices has been shown to be an effective means of integrating excellent electrical conductivity and antifreeze properties. These ions can strongly interact with water molecules to form hydrated ions, lowering the freezing point of water and thus improving the antifreeze properties of hydrogels.

[0004] Silk fibroin is a natural polymer fibrous protein rich in β-pleated crystalline structure. Regenerated silk fibroin is widely used in the preparation of conductive hydrogels due to its excellent biocompatibility, mechanical toughness and degradability. In addition, the mechanical properties and degradation properties of the gel can be effectively adjusted by the secondary structure to meet different practical needs. Existing antifreeze conductive hydrogels derived from SF are mainly achieved by introducing ions and organic solvents.

[0005] The patent with publication number CN115093711 A discloses a method for preparing an antifreeze silk fibroin conductive hydrogel. Silk fibroin-based hydrogel is prepared using silk fibroin, acrylamide, polyethyleneimine, lithium chloride, N,N-methylenebisacrylamide and ammonium persulfate. The hydrogel has antifreeze properties, adhesion and conductivity, and can be used in the fields of biomedicine and electronic devices. The patent with publication number CN114854052 uses polyvinyl alcohol, borax, silk fibroin and tannic acid as components, selects a polyol / water binary solvent that has good compatibility with the above components and has an antifreeze mechanism and is introduced into the hydrogel system to prepare a silk fibroin antifreeze conductive hydrogel, but the entire preparation process is relatively time-consuming and not conducive to industrial production and application.

[0006] The patent with publication number CN 115232478 A prepares a silk / lithium bromide conductive hydrogel pressure sensor, which is composed of a cross-linked silk protein network structure mainly composed of Silk I structure and Li+, and has good softness and electrical response performance. However, the improvement of the conductivity of ionic hydrogels often sacrifices the mechanical properties of the gel [D. Ji, JM Park, MS Oh, TL Nguyen, H. Shin, JS Kim, D. Kim, H S Park, J. Kim, Nature Communications 2022, 13, 3019.]. In addition, under the action of external forces, such as pressure, shear force, etc., as well as changes in the use environment, the displacement and leakage of ions in the gel will occur, which has a significant impact on the conductive stability and service life of the hydrogel. Therefore, it is crucial to establish a strong cross-linked conductive network in the hydrogel.

[0007] In view of this, it is necessary to design an improved antifreeze conductive double network hydrogel based on silk fibroin and its preparation method and application to solve the above problems. Summary of the invention

[0008] In view of the technical problems existing in the background technology, the present application provides an antifreeze conductive double network hydrogel based on silk fibroin and its preparation method and application. In the preparation method, silk fibroin and conductive material can each form a cross-linked network under the action of a cross-linking agent. In addition, there is an intermolecular force between the silk fibroin and the conductive material, which helps to anchor the conductive material in the gel matrix; the formation of the conductive material network can further improve the conductivity of the hydrogel, and the presence of ions and the synergistic effect of the double network structure significantly enhance the antifreeze performance of the gel, and the obtained hydrogel still has good mechanical and sensitive sensing properties at -108°C.

[0009] The hydrogel has the characteristics of simple preparation method, high sensitivity and short response time. The invention provides a new idea for preparing a hydrogel sensor with good ionic conductivity and mechanical properties under extreme conditions.

[0010] In a first aspect, the present invention provides a method for preparing an antifreeze conductive double network hydrogel based on silk fibroin, comprising the following steps:

[0011] S1, mixing the degummed silk with lithium bromide and heating to dissolve, to obtain a silk fibroin / lithium bromide mixed solution;

[0012] S2, adding a conductive substance and a cross-linking agent to the silk fibroin / lithium bromide mixed solution obtained in step S1 to obtain a second mixed solution; and then placing the second mixed solution in an oven for incubation to obtain an antifreeze conductive double network hydrogel based on silk fibroin.

[0013] In the embodiment of the present application, degummed silk is dissolved in lithium bromide solution, and then a conductive material is added and mixed evenly, and cross-linked in the next step under the action of a cross-linking agent to form a silk fibroin conductive hydrogel. Silk fibroin and the conductive material can each form a cross-linked network under the action of a cross-linking agent. In addition, there is an intermolecular force between the silk fibroin and the conductive material, which helps the anchoring of the conductive material in the gel matrix. The high concentration of ions and the conductive network in the gel as conductive media jointly promote the sensing sensitivity and stability of the conductive hydrogel. In addition, lithium bromide can destroy the hydrogen bonding between water molecules, and the formation of a double network significantly reduces the freezing point of the gel system. The hydrogel prepared by the present invention has stable and lossless mechanical properties, conductive sensing performance and ultra-fast response / recovery time under ultra-low temperature conditions, and is suitable for ultra-low temperature environments, such as human motion monitoring in polar expeditions and flexible robots.

[0014] Furthermore, in step S2, the amount of the conductive material is 0.5%-2% of the amount of silk fibroin in the silk fibroin / lithium bromide mixed solution.

[0015] Furthermore, in the second mixed solution, the mass ratio of silk fibroin, conductive material and cross-linking agent is silk fibroin: conductive material: cross-linking agent = 1: (0.5%-2%): (8.0-30%).

[0016] Furthermore, in step S1, in the silk fibroin / lithium bromide mixed solution, the mass fraction of silk fibroin is 1.0-10.0 wt%.

[0017] Furthermore, the concentration of lithium bromide is 7.0-11.0 mol / L.

[0018] Furthermore, the conductive material is one or more of carbon nanotubes, graphene oxide, Mxene, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, polyimide, polyacetylene, polypyrrole, and polyaniline.

[0019] Furthermore, in step S1, during the heating and dissolving treatment, the temperature is 30-120°C, and the reaction time is 0.05-24h. Preferably, the temperature is 45-85°C, and the reaction time is 0.3-4h.

[0020] Furthermore, the cross-linking agent is selected from one or more of polyethylene glycol diglycidyl ether, horseradish peroxidase-H2O2, genipin, polyethylene glycol diglycidyl ether, carbodiimide, glutaraldehyde, 1,4-butanediol diglycidyl ether, tetraiodotetrachlorofluorescein and riboflavin.

[0021] In the second aspect, an embodiment of the present application provides an antifreeze conductive double network hydrogel based on silk fibroin, which is prepared by the aforementioned technical scheme. The antifreeze conductive double network hydrogel based on silk fibroin has a double network structure, and covalent bonds are formed between the chemical crosslinker and the silk fibroin and the conductive substance to form two crosslinked networks.

[0022] The antifreeze conductive double network hydrogel based on silk fibroin is used in the fields of human motion monitoring, climate monitoring, flexible robots, etc. in extremely cold weather such as polar expeditions.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention provides a method for preparing an antifreeze conductive double network hydrogel based on silk fibroin. Lithium bromide is used to destroy the hydrogen bonds between water molecules in the gel to destroy the formation of ice crystals, thereby lowering the freezing point of the gel, thereby achieving the purpose of antifreeze. By separately cross-linking the silk fibroin and the conductive substance to construct a double network structure, it is helpful for the uniform distribution and anchoring of the conductive network in the hydrogel. In addition, there is an electrostatic interaction between the silk fibroin and the conductive substance, and these intermolecular forces all contribute to the stability of the conductive substance network in the gel. At the same time, the dissociated Li + ,Br - The formation of ion pathways increases the conductive pathways in the gel, and the synergistic effect of the two conductive mechanisms significantly improves the conductivity and stability of the sensing performance. That is, adding a crosslinker to chemically crosslink the silk fibroin and the conductive material to construct a double network structure, which improves the conductivity of the conductive hydrogel while giving the gel good mechanical softness and conductive stability.

[0025] (2) Due to the hydrogen bond destroying ability of lithium bromide and the stability of the double network structure in the gel, the gel exhibits good antifreeze performance in an ultra-low temperature environment of -80°C, and its resistance change rate does not change significantly compared to normal temperature, showing good low-temperature sensing performance.

[0026] (3) Compared with traditional silk-based conductive hydrogels, the gel prepared by the present invention has more excellent mechanical properties and elastic recovery rate. It also has the advantages of high deformation sensing sensitivity, wide sensing range, and fast response speed, ensuring reliable and accurate monitoring of human body movements.

[0027] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 Actual pictures of the hydrogels prepared in Examples 1-4 and Comparative Example 1.

[0030] Figure 2 Infrared spectroscopic images of the hydrogels prepared in Examples 1-4 and Comparative Example 1.

[0031] Figure 3 XPS spectra of PEDOT:PSS of the hydrogels prepared in Examples 1-4 and Comparative Example 1 before and after being treated with BDDE.

[0032] Figure 4 This is a comparison chart of the electrical conductivity of the hydrogels prepared in Examples 1-4 and Comparative Example 1.

[0033] Figure 5 This is a physical picture showing the aggregation phenomenon of the silk fibroin / lithium bromide solution after adding conductive material in Comparative Example 2.

[0034] Figure 6 Comparison of the conductivity of the hydrogels prepared in Comparative Example 3 and Example 1 before and after desalination.

[0035] Figure 7 This is a graph of the relative resistance change rate of the hydrogel prepared in Example 1 when attached to the elbow, wrist, finger and knee and subjected to bending cycles.

[0036] Figure 8 This is the DSC curve of the hydrogel prepared in Example 1.

[0037] Fig. 9 The resistance change rate curve of the hydrogel prepared in Example 1 after 1000 continuous loading-unloading cycles at 20% strain at room temperature and -80°C. DETAILED DESCRIPTION

[0038] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0040] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0041] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0042] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0043] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0044] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0045] At present, the improvement of the conductivity of ionic hydrogels often sacrifices the mechanical properties of the gel. In addition, under the action of external forces, such as pressure, shear force, etc., as well as changes in the use environment, the ions in the gel will shift and leak, which will have a significant impact on the conductive stability and service life of the hydrogel. Therefore, it is crucial to establish a strong cross-linked conductive network in the hydrogel.

[0046] The present application provides a method for preparing an antifreeze conductive double network hydrogel based on silk fibroin, comprising the following steps:

[0047] S1, mixing the degummed silk with lithium bromide and heating to dissolve, to obtain a silk fibroin / lithium bromide mixed solution;

[0048] Wherein, the concentration of lithium bromide is 7.0-11.0 mol / L.

[0049] When heating and dissolving, the temperature is 30-120°C and the reaction time is 0.05-24h. Preferably, the temperature is 45-85°C and the reaction time is 0.3-4h.

[0050] In the silk fibroin / lithium bromide mixed solution, the mass fraction of the silk fibroin is 1.0-10.0wt%.

[0051] S2, adding a conductive substance and a cross-linking agent to the silk fibroin / lithium bromide mixed solution obtained in step S1 to obtain a second mixed solution; and then placing the second mixed solution in an oven for incubation to obtain an antifreeze conductive double network hydrogel based on silk fibroin.

[0052] The amount of the conductive material used is 0.5%-2% of the amount of silk fibroin in the silk fibroin / lithium bromide mixed solution.

[0053] In the second mixed solution, the mass ratio of silk fibroin, conductive material and cross-linking agent is silk fibroin: conductive material: cross-linking agent = 1: (0.5%-2%): (8.0-30%).

[0054] The conductive material is one or more of carbon nanotubes, graphene oxide, Mxene, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, polyimide, polyacetylene, polypyrrole, and polyaniline.

[0055] The cross-linking agent is selected from one or more of polyethylene glycol diglycidyl ether, horseradish peroxidase-H2O2, genipin, polyethylene glycol glycidyl ether, carbodiimide, glutaraldehyde, 1,4-butanediol diglycidyl ether, tetraiodotetrachlorofluorescein and riboflavin.

[0056] In the embodiment of the present application, degummed silk is dissolved in lithium bromide solution, and then a conductive material is added and mixed evenly, and cross-linked in the next step under the action of a cross-linking agent to form a silk fibroin conductive hydrogel. Silk fibroin and the conductive material can each form a cross-linked network under the action of a cross-linking agent. In addition, there is an intermolecular force between the silk fibroin and the conductive material, which helps the anchoring of the conductive material in the gel matrix. The high concentration of ions and the conductive network in the gel as conductive media jointly promote the sensing sensitivity and stability of the conductive hydrogel. In addition, lithium bromide can destroy the hydrogen bonding between water molecules, and the formation of a double network significantly reduces the freezing point of the gel system. The hydrogel prepared by the present invention has stable and lossless mechanical properties, conductive sensing performance and ultra-fast response / recovery time under ultra-low temperature conditions, and is suitable for ultra-low temperature environments, such as human motion monitoring in polar expeditions and flexible robots.

[0057] The embodiment of the present application also provides an antifreeze conductive double network hydrogel based on silk fibroin, which is prepared by the aforementioned technical scheme. The antifreeze conductive double network hydrogel based on silk fibroin has a double network structure, and covalent bonds are formed between the chemical crosslinker and the silk fibroin and the conductive substance to form two crosslinked networks.

[0058] The antifreeze conductive double network hydrogel based on silk fibroin is used in the fields of human motion monitoring, climate monitoring, flexible robots, etc. in extremely cold weather such as polar expeditions.

[0059] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0060] Example 1

[0061] A method for preparing an antifreeze conductive double network hydrogel based on silk fibroin comprises the following steps:

[0062] S1, 1.5 g of degummed silk was mixed with 10 mL of 9.3 mol / L lithium bromide and heated at 60° C. to dissolve, and the mixture was evenly mixed to obtain a silk fibroin / lithium bromide blend solution.

[0063] S2, adding a conductive material PEDOT:PSS and a cross-linking agent 1,4-butanediol diglycidyl ether to the silk fibroin / lithium bromide blend solution obtained in step S1 to obtain a second mixed solution; then injecting the second mixed solution into a mold, placing it in an oven for incubation, and obtaining an antifreeze conductive double network hydrogel based on silk fibroin.

[0064] The amount of the conductive material added is 2% of the mass of the silk fibroin in the silk fibroin / lithium bromide blend solution, and the amount of the cross-linking agent added is 15% of the mass of the silk fibroin in the silk fibroin / lithium bromide blend solution;

[0065] That is, in the second mixed solution, the mass ratio of silk fibroin, the conductive substance, and the cross-linking agent is silk fibroin: conductive substance: cross-linking agent = 1:2%:15%.

[0066] Examples 2-4 and Comparative Examples 1-2

[0067] Compared with Example 1, the main difference is that the amount of the conductive material in step S2 is changed, that is, the mass ratio of the silk fibroin, the conductive material, and the crosslinking agent in the second mixed solution is changed; other experimental parameters and conditions are basically the same as those in Example 1, and are not repeated here. The details are shown in the following table.

[0068]

[0069]

[0070] See also Figure 1 Shown are actual pictures of the hydrogels prepared in Examples 1-4 and Comparative Example 1.

[0071] The hydrogels prepared in Examples 1-4 and Comparative Example 1 were tested by infrared spectroscopy. The results are as follows: Figure 2 As shown. It can be seen that the silk peaks are at 1655, 1546, 1511, and 1243 cm -1 The conformation of is mainly random coil, 1605cm -1 The CC stretching vibration mode inside the benzene ring in the fluorene group, 836 cm -1 The peak at ( ) is the stretching vibration peak of CS in PEDOT:PSS, which disappears in the blended gel, indicating the formation of a conductive material network.

[0072] Furthermore, XPS was used to analyze the chemical structure of PEDOT:PSS before and after treatment with 1,4-butanediol diglycidyl ether (BDDE). Figure 3 As shown. It can be seen that after adding BDDE, the S2p nuclear energy level spectrum line has changed significantly. 1S The spectrum shows that after the reaction with BDDE, the binding energy of the sulfonate in PSS increases, and the area of ​​CO (285.7 eV) relative to CC / C=C (283.8 eV) increases significantly, indicating that chemical cross-linking is achieved between the free sulfonic acid of PSS and the epoxide of BDDE. That is, a stable network structure is formed between PEDOT:PSS.

[0073] The conductivity of the hydrogels prepared in Examples 1-4 and Comparative Example 1 was tested by using a Hioki IM3536 LCR in a frequency range of 10 Hz to 10 MHz.

[0074] from Figure 4 It can be seen that the conductivity of silk fibroin hydrogel without conductive material is 9.46S m -1 When the amount of conductive material added is 2%, the conductivity is significantly increased to 16.33S m -1 , indicating that the formation of the conductive material network significantly improves the conductivity of the hydrogel. When the conductive material is further increased to 2.5%, the silk fibroin / lithium bromide solution will undergo obvious aggregation, such as Figure 5 As shown, the highest loading of conductive material is 2.0%.

[0075] Comparative Example 3

[0076] This comparative example provides a method for preparing a hydrogel, which is different from Example 1 in that the gel in Example 1 is desalted to remove lithium bromide from the gel. The remaining steps are basically the same as those in Example 1 and will not be described in detail.

[0077] The hydrogels obtained in Comparative Example 3 and Example 1 were subjected to desalination treatment and then tested for electrical conductivity. The results are as follows: Figure 6 shown.

[0078] It can be seen that compared with the silk fibroin hydrogel without adding conductive substances, the conductivity of the desalted hydrogel only increased slightly by 0.3 S m after adding 2.0% PEDOT:PSS. -1 In contrast, in the presence of LiBr (Example 1), the conductivity increment of the hydrogel significantly increased by 6.87 S m -1 , that is, the addition of 2.0% PEDOT:PSS significantly increased the conductivity by about 23 times.

[0079] It can be seen that the hydrogel prepared by the present invention is mainly ion conductive, and the addition of the PEDOT:PSS network can further significantly improve its conductivity. We speculate that this may be because the multiple conductive pathways constructed by the PEDOT:PSS network and LiBr significantly improve the conductivity of the SPL hydrogel.

[0080] The hydrogel prepared in Example 1 of the present invention was connected to a wire, and then the hydrogel was attached to the elbow, wrist, finger and knee respectively. The elbow, wrist, finger and knee were bent and then returned to their original state (parallel). Multiple bending cycles were performed, and the resistance change of the hydrogel during the stretching of the elbow, wrist, finger and knee was recorded in real time using an electrometer.

[0081] The relative resistance change rate is calculated according to the following formula:

[0082] Relative resistance change rate (%) = △R / R0*100;

[0083] Wherein, R0 is the initial resistance of the hydrogel sample (Ω), and △R is the change in resistance of the hydrogel during stretching of the elbow, wrist, finger, and knee (Ω).

[0084] Figure 7 This is a graph of the relative resistance change rate of the hydrogel obtained in Example 1 of the present invention when it is attached to the elbow, wrist, finger and knee and subjected to bending cycles.

[0085] from Figure 7 It can be seen that after multiple bending cycles, the rate of change of its resistance remains basically stable and has high repeatability. These results show that the hydrogel sensor has good stability and is expected to be used as a wearable strain sensor to detect electrical signals of different body parts.

[0086] Furthermore, in order to verify the low temperature resistance of the conductive hydrogel obtained in Example 1, the freezing point of the sample was further measured by differential scanning calorimetry (DSC, TA Q2000, USA). Figure 8 The freezing point of the hydrogel is shown to be -108°C, indicating that the hydrogel can function effectively in a sub-zero temperature range not exceeding -108°C.

[0087] Furthermore, in order to test the environmental stability and durability of the flexible sensor, the flexible sensor was placed in a room temperature and -80°C environment, and its resistance change rate curve was tested after 1000 consecutive loading-unloading cycles at a strain of 20%. The results are as follows: Fig. 9 shown.

[0088] It can be seen that there is no obvious change in the resistance change rate curves in the initial, middle and final stages of the test, and the relative resistance change rate of the hydrogel flexible sensor to strain does not change much at room temperature and -80°C environment, indicating that the flexible sensor has high environmental stability and excellent durability.

[0089] Examples 5-6 and Comparative Examples 4-5

[0090] Compared with Example 1, the main difference is that the amount of the cross-linking agent in step S2 is changed; other experimental parameters and conditions are basically the same as those in Example 1, and are not repeated here. The details are shown in the following table.

[0091] The compression strength and elastic recovery rate of the obtained hydrogel were tested, and the results are shown in the following table.

[0092]

[0093] As can be seen from the above table, when the content of the crosslinking agent is 8.0-30%, the compressive strength of the gel gradually increases with the gradual increase of the crosslinking agent content; when the content of the crosslinking agent is 15%, it has the highest elastic recovery rate. When the content of the crosslinking agent is 5.0% (Comparative Example 4), the crosslinking density of the gel is relatively low at this time, and its mechanical properties and elastic recovery rate are significantly reduced compared with Example 1, and it is not suitable for use as a strain sensor; when the content of the crosslinking agent is increased to 40% (Comparative Example 5), the crosslinking density of the gel increases significantly, resulting in a significantly higher compressive strength of the gel than that obtained in Example 1, but the elastic recovery rate decreases significantly, only 85.6%, and the flexibility is greatly reduced. When used as a strain sensor, it is not conducive to non-destructive detection of the sensing signal. In addition, it is impossible to make effective electrical signal feedback for small deformations.

[0094] It should be noted that the conductive material may also be one or more of carbon nanotubes, graphene oxide, Mxene, polyimide, polyacetylene, polypyrrole, polyaniline and other conductive materials.

[0095] The cross-linking agent may be one or more of polyethylene glycol diglycidyl ether, horseradish peroxidase-H2O2, genipin, polyethylene glycol glycidyl ether, carbodiimide, glutaraldehyde, 1,4-butanediol diglycidyl ether, tetraiodotetrachlorofluorescein and riboflavin.

[0096] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing an antifreeze conductive double network hydrogel based on silk fibroin, characterized in that: The following steps are involved: S1, mixing degummed silk with lithium bromide and heating to dissolve, to obtain a silk fibroin / lithium bromide mixed solution; S2, adding a conductive substance and a cross-linking agent to the silk fibroin / lithium bromide mixed solution obtained in step S1 to obtain a second mixed solution; and then placing the second mixed solution in an oven for incubation to obtain an antifreeze conductive double network hydrogel based on silk fibroin.

2. The method for preparing the antifreeze conductive double network hydrogel based on silk fibroin according to claim 1, characterized in that: In step S2, the amount of the conductive material used is 0.5%-2% of the amount of silk fibroin in the silk fibroin / lithium bromide mixed solution.

3. The method for preparing the antifreeze conductive double network hydrogel based on silk fibroin according to claim 1, characterized in that: In the second mixed solution, the mass ratio of silk fibroin, conductive material and cross-linking agent is silk fibroin: conductive material: cross-linking agent = 1: (0.5%-2%): (8.0%-30%).

4. The method for preparing the antifreeze conductive double network hydrogel based on silk fibroin according to claim 1, characterized in that: In step S1, in the silk fibroin / lithium bromide mixed solution, the mass fraction of silk fibroin is 1.0-10.0 wt%.

5. The method for preparing the antifreeze conductive double network hydrogel based on silk fibroin according to claim 1, characterized in that: The concentration of the lithium bromide is 7.0-11.0 mol / L.

6. The method for preparing the antifreeze conductive double network hydrogel based on silk fibroin according to claim 1, characterized in that: The conductive material is one or more of carbon nanotubes, graphene oxide, Mxene, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, polyimide, polyacetylene, polypyrrole, and polyaniline.

7. The method for preparing the antifreeze conductive double network hydrogel based on silk fibroin according to claim 1, characterized in that: In step S1, during the heating and dissolution treatment, the temperature is 30 to 120°C and the reaction time is 0.05 to 24 hours.

8. The method for preparing the antifreeze conductive double network hydrogel based on silk fibroin according to claim 1, characterized in that: The cross-linking agent is selected from one or more of polyethylene glycol diglycidyl ether, horseradish peroxidase-H2O2, genipin, polyethylene glycol diglycidyl ether, carbodiimide, glutaraldehyde, 1,4-butanediol diglycidyl ether, tetraiodotetrachlorofluorescein and riboflavin.

9. An antifreeze conductive double network hydrogel based on silk fibroin, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9, the antifreeze conductive double network hydrogel based on silk fibroin has a conductive material cross-linked network and a silk fibroin cross-linked network.

10. An application of an antifreeze conductive double network hydrogel based on silk fibroin, characterized in that: The antifreeze conductive double network hydrogel based on silk fibroin is used in the field of human motion monitoring and flexible robots in polar expedition activities.

Citation Information

Patent Citations

  • Antifreeze silk fibroin conductive hydrogel as well as preparation method and application thereof

    CN115093711A

  • Silk / Li < + > conductive hydrogel pressure sensor and construction method and application thereof

    CN115232478A

  • Silk fibroin / carbon material conductive hydrogel as well as preparation and application thereof

    CN113292744A

  • Silk fibroin-based adhesive anti-freezing conductive hydrogel and preparation method thereof

    CN114133594A

  • Conductive hydrogel, gel ball and preparation method and application thereof

    CN116284861A